Scalability of Web-based electronic commerce systems. - Bochmann, G.V (IEEE Communications magazine)
In a Web-based electronic commerce system, users browse product information offered by an online store and submit requests to purchase selected items. From the user's perspective, response time is a factor that could impact the acceptability of electronic commerce. This article is concerned with system architectures for online stores. Emphasis is placed on techniques to improve a system's capacity to support more users without suffering a noticeable degradation in response time performance. Such techniques have been investigated as part of a Canadian Institute for Telecommunications Research major project entitled Enabling Technology for Electronic Commerce Applications, developed in close collaboration with the IBM® Centre for Advanced Studies. The basic architecture of a Web-based electronic commerce system is first described along with the types of data that need to be managed. Next, an overview of existing techniques for improving system capacity is presented. Finally, highlights of research results obtained as part of the CITR electronic commerce major project are discussed.